The Belt and Road initiative of China: A critical analysis of its feasibility - Horst Löchel; Fahad Nawaz (Frankfurt School of Finance & Management, 2018)
The so-called Belt & Road initiative of China is the largest and most comprehensive global economic activity of our times. It consists on a land as well as a sea channel that covers more than 60 countries in Asia and Europe, around 65 % of the world population, one-third of world's GDP, and 25 % of global trade. Although the project is still in a very early stage it is worth starting a scientific based judgment of its impact and success perspective. This paper aims to kick-off such a discussion by conducting a feasibility study including economic as well as political factors. In order to reduce the complexity of the task the overall project is disaggregated by its six economic corridors plus the sea channel, which are evaluated by the same categories and summarized to an overall result. Our analysis shows that for more than half of the corridors a successful implementation is highly likely, for two the feasibility is judged as medium, and only for one it turns out that a success is unlikely mainly due to political reasons.
Keywords: F02; F15; F21; F53; 330